2016
DOI: 10.1039/c6ra10111a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of solid lipid nanoparticles loaded with cytarabine via a micellar composition for leukemia

Abstract: Cytarabine is an anticancer drug used in hematological malignancies and lymphoma but its short biological half life demands continuous intravenous infusion or time spaced injection. This would lead to patient incompliances and discomfort. Therefore it is imperative to look for novel therapeutic systems with lesser side effects urgently to address the underlying causes of poor treatment outcomes associated with conventional therapy. Hence entrapping of cytarabine in a solid lipid nanoparticle (SLN) based formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Hence, it was attempted to develop FA grafted SLNs bearing OP for targeted delivery to CRC. Tristearin is a biocompatible and biodegradable solid lipid, which has good stability at physiological temperature [14,15]. Therefore, it was selected to prepare lipid matrix of SLNs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it was attempted to develop FA grafted SLNs bearing OP for targeted delivery to CRC. Tristearin is a biocompatible and biodegradable solid lipid, which has good stability at physiological temperature [14,15]. Therefore, it was selected to prepare lipid matrix of SLNs.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Li et al 19 synthesized a drug, 5-FU loaded chitosan-coated ZnSe/ZnS NPs (5-Fu–CS–ZnSe/ZnS NPs) and observed that the XRD plot of 5-FU displayed diffraction peaks indicating its crystalline nature, however, no such peak of the drug was obtained in the XRD of 5-Fu–CS–ZnSe/ZnS NPs depicting that the drug was present in its amorphous form onto the functionalized NPs. Raj et al 20 prepared solid-lipid NPs and loaded them with cytarabine, an anticancer drug meant for treating leukemia. The XRD plot obtained for cytarabine was crystalline in nature, but the XRD pattern of the cytarabine-loaded solid-lipid NPs did not show the characteristic peak of cytarabine.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment includes a combination of chemotherapy, targeted therapy, radiation therapy, bone marrow transplantation, and palliative care. Certain types of leukemia are treated with conscious anticipation 40) . Blood or platelet products, as well as a pain clinic, may be needed.…”
Section: Anti-cancer Resultsmentioning
confidence: 99%